BULLYING DI SEKOLAH DASAR DALAM PERSPEKTIF GENDER - Alimuddin, Johar (Yinyang: Jurnal Studi Islam Gender dan Anak, 2017)
Bullying is a problem occurring in many schools, including in elementary schools. It is in relation to gender because both focus on oppression. Talking about bullying in relation to oppression is broader than that of gender because in gender study, it is merely viewed based on gender differences. Gender and bullying are interrelated even though gender is not a significant factor causing bullying. In elementary schools, bullying is caused by seniority more than gender factor. To minimize bullying in elementary schools, it is necessary to raise empathy among the students and to handle it from the perspective of age or seniority, not gender.